Primary Lung Cystic Adenoid Tumor With Extensive Involvement Of The Right Lung And Distal Trachea Treated With Tracheal Sleeve Pneumonectomy: A Case Report (2016)
Cystic adenoid carcinoma is a tumor with low-grade malignancy of slow growth original from salivary glands, which can appear in the central airway and extend to the lung. Even though its slow growth and discrete invasion, its localization may cause obstruction with severe compromise, we present the case of a patient with right lung cystic adenoid tumor with invasion of the carina, distal trachea and contralateral nodules treated with pneumonectomy and carinal resection with an adequate response